Use of liver stiffness measurement for liver resection surgery: correlation with indocyanine green clearance testing and post-operative outcome. - James Fung (Public Library of Science (PLoS), 2013)
Background Liver stiffness measurement (LSM) using transient elastography has recently become available for the assessment of liver fibrosis. Whether LSM can predict the functional liver reserve in patients undergoing liver resection is not certain. Aim To correlate liver stiffness measurement (LSM) with indocyanine green (ICG) clearance test and liver biochemistry, and to determine its usefulness in predicting postoperative outcomes in patients undergoing liver resection. Patients and methods Transient elastography and ICG clearance test were performed pre-operatively in 44 patients with hepatocellular carcinoma. The LSM and ICG retention rate at 15 minutes (R15) were correlated with pre-operative factors and post-operative outcomes. Results There was significant correlation between ICG R15 and LSM. In patients with LSM ≥11 kPa vs <11 kPa, there was significantly higher ICG R15 (17.1% vs 10.0% respectively, p = 0.025). For patients with ICG R15≥10% compared to those <10%, there was significantly higher LSM (12.0 vs 7.6 kPa respectively, p = 0.015). Twenty-eight patients proceeded to resection. There was a significant correlation between LSM and the peak INR after liver resection (r = 0.426, p = 0.024). There was a significant correlation between ICG R15 and the post-operative peak AST level (r = -0.414, p = 0.029) and peak ALT level (r = -0.568, p = 0.002). The operative time was a significant independent factor associated with post-operative complications and peak INR. Conclusion LSM correlated well with ICG R15 in patients undergoing liver resection, and predicted early post-operative complications. Addition of LSM to ICG R15 testing may provide better prognostic information for patients undergoing resection.